FAS engagement drives apoptosis of enterocytes of coeliac patients. Issue 3 (1st March 2001) - Maiuri, L; Ciacci, C; Raia, V; Vacca, L; Ricciardelli, I; Raimondi, F; Auricchio, S; Quaratino, S; Londei, M
Abstract : BACKGROUND: Villus atrophy is the most distinctive sign of untreated coeliac disease (CD) and epithelial apoptosis is considered to be involved in this stage of the coeliac lesion. The extent of villus atrophy is, however, not homogeneous and patients with patchy or mild lesions have been described. AIMS: To address: (a) the degree of "patchiness" in untreated CD patients; and (b) to clarify if apoptosis, and eventually which trigger drives it, causes epithelial damage. PATIENTS: Twenty of 40 untreated, 14 treated coeliac patients, and 15 controls received five or more multiple duodenal biopsies; the remaining 20 untreated CD patients had no more than three biopsies. METHODS: All biopsies were analysed to monitor the presence of a "flat" mucosa. Biopsies of 14 untreated, 10 treated coeliacs, and seven controls were cultured with or without gliadin. DNA fragmentation was studied by terminal deoxynucleotidyl transferase (TdT) mediated dUTP digoxigenin nick end labelling (TUNEL), and FAS and Ki67 expression by immunohistochemistry. Antiendomysium antibodies (EMA) were surveyed in biopsy culture supernatants. RESULTS: A pattern of patchy duodenal lesions was observed in all untreated CD patients biopsied up to five times. High enterocyte FAS expression, and a high number of TUNEL+ and Ki67+ enterocytes were detected in areas with villus atrophy but not in those with a normal morphology (p<0.001). Conversely, EMA in culture supernatants and signs of immunological activation were present in all untreated CD biopsies. In vitro gliadin challenge increased the number of TUNEL+ and Ki67+ enterocytes (p<0.001 v cultures with medium alone) only in "flat" biopsies. Neutralising anti-FAS monoclonal antibodies were found to control gliadin induced enterocyte apoptosis (p>0.01) while agonist anti-FAS monoclonal antibody increased it (p<0.001). CONCLUSIONS: Patchy lesions are observed in untreated CD mucosa and epithelial FAS engagement is a key trigger in driving villus atrophy in CD.